Food restriction induces in vivo ventricular dysfunction in spontaneously hypertensive rats without impairment of in vitro myocardial contractility - Okoshi, Katashi [UNESP]; Fioretto, J.R. [UNESP]; Okoshi, M.P. [UNESP]; Cicogna, A.C. [UNESP]; Aragon, Flávio Ferrari [UNESP]; Matsubara, L.S. [UNESP]; Matsubara, B.B. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2004)
Cardiac structures, function, and myocardial contractility are affected by food restriction (FR). There are few experiments associating undernutrition with hypertension. The aim of the present study was to analyze the effects of FR on the cardiac response to hypertension in a genetic model of hypertension, the spontaneously hypertensive rat (SHR). Five-month-old SHR were fed a control or a calorie-restricted diet for 90 days. Global left ventricle (LV) systolic function was evaluated in vivo by transthoracic echocardiogram and myocardial contractility and diastolic function were assessed in vitro in an isovolumetrically beating isolated heart (Langendorff preparation). FR reduced LV systolic function (control (mean ± SD): 58.9 ± 8.2; FR: 50.8 ± 4.8%, N = 14, P < 0.05). Myocardial contractility was preserved when assessed by the +dP/dt (control: 3493 ± 379; FR: 3555 ± 211 mmHg/s, P > 0.05), and developed pressure (in vitro) at diastolic pressure of zero (control: 152 ± 16; FR: 149 ± 15 mmHg, N = 9, P > 0.05) and 25 mmHg (control: 155 ± 9; FR: 150 ± 10 mmHg, N = 9, P > 0.05). FR also induced eccentric ventricular remodeling, and reduced myocardial elasticity (control: 10.9 ± 1.6; FR: 9.2 ± 0.9%, N = 9, P < 0.05) and LV compliance (control: 82.6 ± 16.5; FR: 68.2 ± 9.1%, N = 9, P < 0.05). We conclude that FR causes systolic ventricular dysfunction without in vitro change in myocardial contractility and diastolic dysfunction probably due to a reduction in myocardial elasticity.
Keywords: Undernutrition; Isolated heart; Echocardiogram; Langendorff preparation; Ventricular remodeling